2021
DOI: 10.1021/acsami.1c01860
|View full text |Cite
|
Sign up to set email alerts
|

Superior Conversion Efficiency Achieved in GeP3/h-BN Heterostructures as Novel Flexible and Ultralight Thermoelectrics

Abstract: GeP3 materials are attracting broad research interest due to their typical puckered layer structure, high carrier mobility, and chemical stability. This peculiarity expedites the independent control of anisotropic electrical and thermal conductance, which is thus expected to possess great thermoelectric potential. Nevertheless, the metal characteristics of GeP3 in the bulk and thick films are adverse to real application because of the low Seebeck coefficient. Thus, it is highly desirable to explore effective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…One approach to enlarge the band gap of GeP 3 is capping 2D h-BN layer as an insulating material, preserving the in-plane electrical conductance of GeP 3 . As illustrated in Figure 9b-e, GeP 3 is an indirect bandgap material with E g of 0.23 and 0.12 eV for monolayer (1L) and bilayer (2L) GeP 3 , respectively [141]. These values increase to 0.34 eV when a monolayer 2D h-BN is inserted.…”
Section: Thermoelectricsmentioning
confidence: 90%
See 1 more Smart Citation
“…One approach to enlarge the band gap of GeP 3 is capping 2D h-BN layer as an insulating material, preserving the in-plane electrical conductance of GeP 3 . As illustrated in Figure 9b-e, GeP 3 is an indirect bandgap material with E g of 0.23 and 0.12 eV for monolayer (1L) and bilayer (2L) GeP 3 , respectively [141]. These values increase to 0.34 eV when a monolayer 2D h-BN is inserted.…”
Section: Thermoelectricsmentioning
confidence: 90%
“…Recently, it was shown that heterostructures of 2D h-BN and 2D GeP 3 can be promising thermoelectric materials [141]. Pristine GeP 3 depicts supreme charge carrier mobility and good chemical stability; however, its small bandgap degrades the thermoelectric characteristics.…”
Section: Thermoelectricsmentioning
confidence: 99%
“…GeP, GeP 3 , GeP 5 ). [27][28][29][30] Recently, we reported a reversible superconductivity up to the maximum value of 10.5 K at 13.5 GPa during the 2D to 3D structural transition in GeP 5 . 31 More interestingly, a significant phonon softening in the Raman spectrum was observed because of the extension of the inplane P-P bonds.…”
Section: Introductionmentioning
confidence: 98%
“…In the GeP 3 /h‐BN heterostructure, by applying 5% tensile strain to adjust the CB structure, a large ZT value of 1.15 at 300 K can be reached for the n‐type heterostructure. For p‐type doping, the highest ZT value of 5.13 was predicted at room temperature in the GeP 3 /h‐BN heterostructure 550 …”
Section: Applications Of Ge‐based 2d Materialsmentioning
confidence: 99%
“…For p-type doping, the highest ZT value of 5.13 was predicted at room temperature in the GeP 3 /h-BN heterostructure. 550 F I G U R E 2 4 Solar cells. (A) Schematic configuration of CdS/GeSe superstrate solar cell.…”
Section: Thermoelectric Devicesmentioning
confidence: 99%